Pengaruh Media Pembelajaran Aplikasi Geogebra Terhadap Hasil Belajar Siswa - Al Ikhlas; Trisna Rukhmana; Wa Ode Feti Liliana (Departement of Mathematics Education, 2023)
Based on the results of the author's initial observations on December 21, 2022 at SMP Negeri 7 Kerinci in class VIII carrying out individual tasks, there are still students who cheat. In addition, the lack of learning planning from teachers by choosing a mathematical learning model that suits the learning style of students, the need for consideration for teachers of the nature of mathematics subjects in carrying out learning to students. The purpose of this study is to influence the learning media of geogebra applications on the critical thinking ability of mathematics students of SMP Negeri 7 Kerinci class VIII. Based on the problem to be studied, namely to see the influence of mathematics learning outcomes of students who are taught using geogebra learning media in class VIII of SMP N 7 Kerinci, this research is a quantitative research with a quasi-experimental approach. The design used in this study is the One Group Pretest Post Test. The data analysis used in this study includes normality, homogeneity and hypothesis tests. Based on the pretest and postest that the author did, the average score of students' mathematics learning outcomes was 70.14 and 77.46, respectively. The average posttest score is higher than the average pretest score of students. Furthermore, based on data analysis using the t-test, a significance value (p-value) of < ∝ or in other words 0.000 < 0.05 means that H1 is accepted or in other words there is an influence of geogebra learning media on mathematics learning outcomes of grade VIII students of SMP Negeri 7 Kerinci.